Does one size fit all? Value-based subcultures and leadership preferences in Turkey - Kuzulugil, Şebnem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
The goal of this study is to explore how Turkish people think about a leader, to identify the dimensions of the implicit Turkish concept of leadership, and to examine whether different cultural groups within Turkey differ in their perceptions of implicit leadership traits. The value dimensions specified in analyses are achievement, funseeking, fatalism, benevolence, universalism and conformity. Values are measured through a 29-item Likert-type scale. Preferred leadership attributes, i.e. implicit leadership theories are measured through a 50-item Likerttype scale measuring six leadership factors, participative paternalism, humane activism, aggressiveness, diplomacy, ambition and conventionalism. Snowball sampling produced 400 usable surveys from all geographic regions of Turkey except Southeast Anatolia. Cluster analysis of value orientations revealed three distinct value-based subcultures within the sample. These subcultures differed in their demographic attributes and leadership preferences as well as value orientations as expected. The relationship between demographic variables, value orientations and leadership preferences were examined mainly through extensive multiple regression analyses. Analysis results suggest that demographic attributes are somewhat predictive of value orientations and value orientations in turn affect leadership preferences. Though subcultures did differ in their leadership preferences, analysis results show that the rank ordering of most preferred leadership attributes did not change among subcultures, suggesting the existence of a Turkish Implicit Leadership Theory. Education level of the respondents was shown to affect both value orientations and leadership preferences.
Keywords: Leadership.; Likert scale.